Solving quadratic equations by factorization method
Exercise 12.2
1. Solve :
(a) x² - 3x = 0Solution:
Here,
x² - 3x = 0
or, x(x - 3) = 0
Either, x = 0
∴ x = 0
or (x - 3) = 0
∴ x = 3
Hence, the values of x are 0 and 3.
(b) 2x² - x = 0Solution:
Here,
2x² - x = 0
or, x(2x - 1) = 0
Either, x = 0
∴ x = 0
or (2x - 1) = 0
∴ x = 1/2
Hence, the values of x are 0 and 1/2.
(c) 9x² + 3x = 0Solution:
Here,
9x² + 3x = 0
or, x(9x + 3) = 0
Either, x = 0
∴ x = 0
or (9x + 3) = 0
∴ x = -1/3
Hence, the values of x are 0 and -1/3.
(d) 9y² - 4 = 0Solution:
Here,
9y² - 4 = 0
or, (3y - 2)(3y + 2) = 0
Either, (3y - 2) = 0
∴ y = 2/3
or (3y + 2) = 0
∴ y = -2/3
Hence, the values of y are 2/3 and -2/3.
(e) 5x + 9x² = 0Solution:
Here,
5x + 9x² = 0
or, x(5 + 9x) = 0
Either, x = 0
∴ x = 0
or (5 + 9x) = 0
∴ x = -5/9
Hence, the values of x are 0 and -5/9.
(f) 4y² - 7y = 0Solution:
Here,
4y² - 7y = 0
or, y(4y - 7) = 0
Either, y = 0
∴ y = 0
or (4y - 7) = 0
∴ y = 7/4
Hence, the values of y are 0 and 7/4.
(g) x² - 49 = 0Solution:
Here,
x² - 49 = 0
or, (x - 7)(x + 7) = 0
Either, (x - 7) = 0
∴ x = 7
or (x + 7) = 0
∴ x = -7
Hence, the values of x are 7 and -7.
(h) 169x² - 96 = 0Solution:
Here,
169x² - 96 = 0
or, x² = 96/169
∴ x = ±√(96/169)
∴ x = ±(4√6)/13
Hence, the values of x are (4√6)/13 and -(4√6)/13.
(i) x²/4 - 36 = 0Solution:
Here,
x²/4 - 36 = 0
or, x²/4 = 36
∴ x² = 144
∴ x = ±12
Hence, the values of x are 12 and -12.
(j) 5x² - 125 = 0Solution:
Here,
5x² - 125 = 0
or, 5(x² - 25) = 0
∴ (x² - 25) = 0
or, (x - 5)(x + 5) = 0
Either, (x - 5) = 0
∴ x = 5
or (x + 5) = 0
∴ x = -5
Hence, the values of x are 5 and -5.
(k) x² - 7 = 29Solution:
Here,
x² - 7 = 29
or, x² = 29 + 7
∴ x² = 36
∴ x = ±6
Hence, the values of x are 6 and -6.
(l) x² - 4x = 0Solution:
Here,
x² - 4x = 0
or, x(x - 4) = 0
Either, x = 0
∴ x = 0
or (x - 4) = 0
∴ x = 4
Hence, the values of x are 0 and 4.
2. Solve : (a) x² - 3x = 0Solution:
Here,
x² - 3x = 0
or, x (x - 3) = 0
Either, x = 0
∴ x = 0
or (x - 3) = 0
∴ x = 3
Hence, the values of x are 0 and 3.
(b) 2x² - x = 0Solution:
Here,
2x² - x = 0
or, x(2x - 1) = 0
Either, x = 0
∴ x = 0
or (2x - 1) = 0
∴ x = 1/2
Hence, the values of x are 0 and 1/2.
(c) 9x² + 3x = 0Solution:
Here,
9x² + 3x = 0
or, x (9x + 3) = 0
Either, x = 0
∴ x = 0
or (9x + 3) = 0
∴ x = -1/3
Hence, the values of x are 0 and -1/3.
(d) 9y² - 4 = 0Solution:
Here,
9y² - 4 = 0
or, (3y - 2)(3y + 2) = 0
Either, (3y - 2) = 0
∴ y = 2/3
or (3y + 2) = 0
∴ y = -2/3
Hence, the values of y are 2/3 and -2/3.
(e) 5x + 9x² = 0Solution:
Here,
5x + 9x² = 0
or, x(5 + 9x) = 0
Either, x = 0
∴ x = 0
or (5 + 9x) = 0
∴ x = -5/9
Hence, the values of x are 0 and -5/9.
(f) 4y² - 7y = 0Solution:
Here,
4y² - 7y = 0
or, y(4y - 7) = 0
Either, y = 0
∴ y = 0
or (4y - 7) = 0
∴ y = 7/4
Hence, the values of y are 0 and 7/4.
(g) x² - 49 = 0Solution:
Here,
x² - 49 = 0
or, (x - 7)(x + 7) = 0
Either, (x - 7) = 0
∴ x = 7
or (x + 7) = 0
∴ x = -7
Hence, the values of x are 7 and -7.
(h) 169x² - 96 = 0Solution:
Here,
169x² - 96 = 0
or, x² = 96/169
∴ x = ±√(96/169)
∴ x = ±(4√6)/13
Hence, the values of x are (4√6)/13 and -(4√6)/13.
(i) x²/4 - 36 = 0Solution:
Here,
x²/4 - 36 = 0
or, x²/4 = 36
∴ x² = 144
∴ x = ±12
Hence, the values of x are 12 and -12.
(j) 5x² - 125 = 0Solution:
Here,
5x² - 125 = 0
or, 5(x² - 25) = 0
∴ (x² - 25) = 0
or, (x - 5)(x + 5) = 0
Either, (x - 5) = 0
∴ x = 5
or (x + 5) = 0
∴ x = -5
Hence, the values of x are 5 and -5.
(k) x² - 7 = 29Solution:
Here,
x² - 7 = 29
or, x² = 29 + 7
∴ x² = 36
∴ x = ±6
Hence, the values of x are 6 and -6.
(l) x² - 4x = 0Solution:
Here,
x² - 4x = 0
or, x(x - 4) = 0
Either, x = 0
∴ x = 0
or (x - 4) = 0
∴ x = 4
Hence, the values of x are 0 and 4.
(m) x² - 6x + 8 = 0Solution:
Here,
x² - 6x + 8 = 0
or, x² - 4x - 2x + 8 = 0
or, x(x - 4) - 2(x - 4) = 0
or, (x - 4)(x - 2) = 0
Either, (x - 4) = 0
∴ x = 4
or (x - 2) = 0
∴ x = 2
Hence, the values of x are 4 and 2.
(n) 2x² - x - 6 = 0Solution:
Here,
2x² - x - 6 = 0
or, 2x² - 4x + 3x - 6 = 0
or, 2x(x - 2) + 3(x - 2) = 0
or, (2x + 3)(x - 2) = 0
Either, (2x + 3) = 0
∴ x = -3/2
or (x - 2) = 0
∴ x = 2
Hence, the values of x are -3/2 and 2.
(o) y² + 7y + 12 = 0Solution:
Here,
y² + 7y + 12 = 0
or, y² + 4y + 3y + 12 = 0
or, y(y + 4) + 3(y + 4) = 0
or, (y + 4)(y + 3) = 0
Either, (y + 4) = 0
∴ y = -4
or (y + 3) = 0
∴ y = -3
Hence, the values of y are -4 and -3.
(p) 7x² + 13x - 2 = 0Solution:
Here,
7x² + 13x - 2 = 0
or, 7x² + 14x - x - 2 = 0
or, 7x(x + 2) - 1(x + 2) = 0
or, (7x - 1)(x + 2) = 0
Either, (7x - 1) = 0
∴ x = 1/7
or (x + 2) = 0
∴ x = -2
Hence, the values of x are 1/7 and -2.
(q) x² + 9x - 22 = 0Solution:
Here,
x² + 9x - 22 = 0
or, x² + 11x - 2x - 22 = 0
or, x(x + 11) - 2(x + 11) = 0
or, (x + 11)(x - 2) = 0
Either, (x + 11) = 0
∴ x = -11
or (x - 2) = 0
∴ x = 2
Hence, the values of x are -11 and 2.
(r) x² - 18x + 77 = 0Solution:
Here,
x² - 18x + 77 = 0
or, x² - 11x - 7x + 77 = 0
or, x(x - 11) - 7(x - 11) = 0
or, (x - 11)(x - 7) = 0
Either, (x - 11) = 0
∴ x = 11
or (x - 7) = 0
∴ x = 7
Hence, the values of x are 11 and 7.
(s) 2x² + 11x + 12 = 0Solution:
Here,
2x² + 11x + 12 = 0
or, 2x² + 8x + 3x + 12 = 0
or, 2x(x + 4) + 3(x + 4) = 0
or, (2x + 3)(x + 4) = 0
Either, (2x + 3) = 0
∴ x = -3/2
or (x + 4) = 0
∴ x = -4
Hence, the values of x are -3/2 and -4.
(t) 3x² - 11x - 20 = 0Solution:
Here,
3x² - 11x - 20 = 0
or, 3x² - 15x + 4x - 20 = 0
or, 3x(x - 5) + 4(x - 5) = 0
or, (3x + 4)(x - 5) = 0
Either, (3x + 4) = 0
∴ x = -4/3
or (x - 5) = 0
∴ x = 5
Hence, the values of x are -4/3 and 5.
(u) 10x² + 19x + 6 = 0Solution:
Here,
10x² + 19x + 6 = 0
or, 10x² + 15x + 4x + 6 = 0
or, 5x(2x + 3) + 2(2x + 3) = 0
or, (5x + 2)(2x + 3) = 0
Either, (5x + 2) = 0
∴ x = -2/5
or (2x + 3) = 0
∴ x = -3/2
Hence, the values of x are -2/5 and -3/2.
(v) 12x² - 11x + 2 = 0Solution:
Here,
12x² - 11x + 2 = 0
or, 12x² - 8x - 3x + 2 = 0
or, 4x(3x - 2) - 1(3x - 2) = 0
or, (4x - 1)(3x - 2) = 0
Either, (4x - 1) = 0
∴ x = 1/4
or (3x - 2) = 0
∴ x = 2/3
Hence, the values of x are 1/4 and 2/3.
(w) 3z² - 11z + 6 = 0Solution:
Here,
3z² - 11z + 6 = 0
or, 3z² - 9z - 2z + 6 = 0
or, 3z(z - 3) - 2(z - 3) = 0
or, (3z - 2)(z - 3) = 0
Either, (3z - 2) = 0
∴ z = 2/3
or (z - 3) = 0
∴ z = 3
Hence, the values of z are 2/3 and 3.
(x) (x + 1)² - 4 = 0Solution:
Here,
(x + 1)² - 4 = 0
or, (x + 1 - 2)(x + 1 + 2) = 0
or, (x - 1)(x + 3) = 0
Either, (x - 1) = 0
∴ x = 1
or (x + 3) = 0
∴ x = -3
Hence, the values of x are 1 and -3.
(y) (p + 3)² - 16 = 0Solution:
Here,
(p + 3)² - 16 = 0
or, (p + 3 - 4)(p + 3 + 4) = 0
or, (p - 1)(p + 7) = 0
Either, (p - 1) = 0
∴ p = 1
or (p + 7) = 0
∴ p = -7
Hence, the values of p are 1 and -7.
(z) (x + 6)² - 36 = 0Solution:
Here,
(x + 6)² - 36 = 0
or, (x + 6 - 6)(x + 6 + 6) = 0
or, x(x + 12) = 0
Either, x = 0
or (x + 12) = 0
∴ x = -12
Hence, the values of x are 0 and -12.
(aa) (x - 7)² - 64 = 0Solution:
Here,
(x - 7)² - 64 = 0
or, (x - 7 - 8)(x - 7 + 8) = 0
or, (x - 15)(x + 1) = 0
Either, (x - 15) = 0
∴ x = 15
or (x + 1) = 0
∴ x = -1
Hence, the values of x are 15 and -1.
(ab) 100 - (x - 5)² = 0Solution:
Here,
100 - (x - 5)² = 0
or, (10 + x - 5)(10 - x + 5) = 0
or, (x + 5)(15 - x) = 0
Either, (x + 5) = 0
∴ x = -5
or (15 - x) = 0
∴ x = 15
Hence, the values of x are 15 and -5.
(3a) Find the quadratic equation whose roots (value of x) are 1 and 2.Solution:
The standard form of a quadratic equation is:
x² - (sum of roots)x + (product of roots) = 0
Here, roots are 1 and 2.
Sum of roots = 1 + 2 = 3
Product of roots = 1 × 2 = 2
Therefore, the quadratic equation is:
x² - 3x + 2 = 0
(4b) Find the quadratic equation whose roots (value of x) are 3 and -2.Solution:
The standard form of a quadratic equation is:
x² - (sum of roots)x + (product of roots) = 0
Here, roots are 3 and -2.
Sum of roots = 3 + (-2) = 1
Product of roots = 3 × (-2) = -6
Therefore, the quadratic equation is:
x² - 1x - 6 = 0
or, x² - x - 6 = 0
(5c) Find the quadratic equation whose roots (value of y) are 3 and -2.Solution:
The standard form of a quadratic equation is:
y² - (sum of roots)y + (product of roots) = 0
Here, roots are 3 and -2.
Sum of roots = 3 + (-2) = 1
Product of roots = 3 × (-2) = -6
Therefore, the quadratic equation is:
y² - 1y - 6 = 0
or, y² - y - 6 = 0
No comments:
Post a Comment